MAPPING CHARACTER EDUCATION VALUES IN SUCIATI’S MENITI ASA THROUGH THOMAS LICKONA’S TEN ESSENTIAL VIRTUES - Juli Novia Purba; Hidayatun Nur (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study aims to map the character education values represented in Suciati’s novel Meniti Asa through Thomas Lickona’s framework of ten essential virtues. This research is important because the novel portrays the moral struggles of adolescents in conditions of economic hardship, family conflict, and social pressure, making it relevant to contemporary character education discourse. The study employed a qualitative descriptive method using content analysis. The data source was the novel Meniti Asa published in 2021 by PT Inti Prima Aksara. Data were collected through hermeneutic reading techniques involving reading, note-taking, classification, and interpretation. The findings reveal 120 data points representing character education values, consisting of wisdom, justice, fortitude, self-control, love, positive attitude, hard work, integrity, gratitude, and humility. Among these values, fortitude emerged as the most dominant virtue, followed by love and positive attitude. Nayla’s moral development reflects resilience, empathy, responsibility, emotional maturity, and self-awareness throughout the conflicts she experiences. The study also demonstrates that Meniti Asa possesses strong pedagogical relevance as a literary medium for strengthening character education in literature learning. Therefore, the novel contributes not only as literary entertainment but also as a meaningful source of moral learning in educational contexts.